Perlakuan Alkali Dan Variasi Fraksi Berat Serat Terhadap Karakteristik Kekuatan Tarik Komposit Polyester Berpenguat Serat Bambu Tabah - Harsa Nadi, I Made Dwi Pica; Tirta Nindhia, Tjokorda Gde; Adnyana, I Wayan Bandem (Teknik Desain Mekanika, 2022)
Abstract Technological developments in manufacturing and the increasing need for metal materials have led to the scarcity of materials available in nature. For this reason, a lot of research and development has been carried out on natural fiber-reinforced composites that have mechanical properties that can compensate for the properties and advantages of metal materials. The material used in this research is Yukalac 157 BQTN-EX polyester with the addition of 1% (v/v) MEKPO catalyst. This study uses natural fibers derived from the tabah bamboo tree (gigantochloa nigrociliata). Tough bamboo fiber is obtained from the process of separating the skin from the bamboo flesh using the water retting extraction method. The fibers were then treated with NaOH with variations of 0%, 2%, 5%, and 7% for 2 hours of immersion. The fiber with the highest strength was used for composite printing using the hand lay up technique with variations in fiber weight fraction of 0%, 5%, 10%, 15%, and 20% used random fiber orientation with a fiber length of 30 mm. Composite cuts conform to ASTM D 638 standards for Tensile tests. The results showed that the resilient bamboo fiber that obtained the highest single fiber tensile strength was found in the 5% NaOH treatment for 2 hours, namely 406.43 MPa and the highest tensile strength of the polyester composite reinforced with tough bamboo fiber was found in the 20% fiber weight fraction with an average value. of 32.59 MPa, and the lowest value of 13.15 MPa at 0% fiber weight fraction. then the result is an increase in the tensile strength of the composite along with an increase in the given weight fraction. Keywords : Tabah bamboo fiber, single fiber, tensile strength, fiber weight fraction